Semaphorin 3A Is Effective in Reducing Both Inflammation and Angiogenesis in a Mouse Model of Bronchial Asthma - Adi, Sabag D.; Eiza, Nasren; Bejar, Jacob; Shefer, Hila; Toledano, Shira; Kessler, Ofra; Neufeld, Gera; Toubi, Elias; Vadasz, Zahava (Frontiers in Immunology, 2019)
Semaphorin 3A (sema3A) belongs to the sub-family of the immune semaphorins that function as regulators of immune-mediated inflammation. Sema3A is a membrane associated molecule on T regulatory cells and on B regulatory cells. Being transiently ligated to the cell surface of these cells it is suggested to be a useful marker for evaluating their functional status. In earlier studies, we found that reduced sema3A concentration in the serum of asthma patients as well as reduced expression by Treg cells correlates with asthma disease severity. Stimulation of Treg cells with recombinant sema3A induced a significant increase in FoxP3 and IL-10 expression. To find out if sema3A can be of benefit to asthma patients, we evaluated the effect of sema3A injection in a mouse model of asthma. BALB\c-mice were sensitized using ovalbumin (OVA) + adjuvant for 15 days followed by OVA aerosol inhalation over five consecutive days. Four hours following air ways sensitization on each of the above days- 15 of these mice were injected intraperitoneally with 50 μg per mouse of recombinant human sema3A-FR and the remaining 15 mice were injected with a similarly purified vehicle. Five days later the mice were sacrificed, broncheo-alveolar lavage (BAL) was collected and formalin-fixed lung biopsies taken and analyzed. In sema3A treated mice, only 20% of the bronchioles and arterioles were infiltrated by inflammatory cells as compared to 90% in the control group (P=0.0079). In addition, eosinophil infiltration was also significantly increased in the control group as compared with the sema3A treated mice. In sema3A treated mice we noticed only a small number of mononuclear and neutrophil cells in the BAL while in the control mice, the BAL was enriched with mononuclear and neutrophil cells. Finally, in the control mice, angiogenesis was significantly increased in comparison with sema3A treated mice as evidenced by the reduced concentration of microvessels in the lungs of sema3A treated mice. To conclude, we find that in this asthma model, sema3A functions as a potent suppressor of asthma related inflammation that has the potential to be further developed as a new therapeutic for the treatment of asthma.